LIKUIDITAS, PROFITABILITAS, LEVERAGE TERHADAP HARGA SAHAM PERUSAHAAN SUBSEKTOR TRANSPORTASI DI BURSA EFEK INDONESIA - Cut Aldira Bunga Nanggro; Zulfikar Ramadhan (Media Riset Bisnis Ekonomi Sains dan Terapan, 2026)
This study examines the effect of liquidity, profitability, and leverage on stock prices of transportation subsector companies listed on the Indonesia Stock Exchange (IDX). The research aims to analyze how these financial performance indicators influence stock price movements during the post-pandemic period. This study employs a quantitative correlational approach using secondary data obtained from the financial statements of transportation subsector companies for the 2021–2024 period. The population consists of 13 companies, with 11 companies selected through purposive sampling. Data analysis was conducted using panel data multiple linear regression with EViews 12, and the selected estimation model was the random effects model. The results indicate that liquidity has a significant negative effect on stock prices, profitability has a negative but insignificant effect, and leverage has a positive but insignificant effect on stock prices. These findings suggest that investors should carefully reassess financial ratios when making investment decisions, while companies are encouraged to optimize their financial performance to enhance stock value in the capital market.Keywords: Leverage, Liquidity, Profitability, Stock Price